ESTABLISHING MICROSOFT RESEARCH CENTRE IN INDONESIA: A ROAD PATH TOWARD EXPORTING INDONESIAN SOFTWARE - Nurhajati Ma'mun; Wawan Dhewanto; Ronaldi Ronaldi; Kridanto Surendro; Basuki Sugiharto (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2006)
Entering the 21st century, information and communication technolou (ICT) has become an un-separated part in daily human activities. ICT business has become the means in creating wealth and welfare for those commanding this technology. Indonesia with her abundance of people could have compete and create a mass of entrepreneurs in the ICT business. Lack of human development and other causes have brought Indonesia to become merely just user and buyer in the thriving business. The Government of Indonesia has long realized this and has made some efforts in closing the gap. President Yudhoyono 's visit the USA in 2005 has brought an early discussion whether Microsoft will open its research centre in Indonesia. The discussion arouse to a level that in the future Indonesia would able to export its software to the world market. There are steps to be taken and resources to be prepared. There are certain constrains for Indonesia to rise as the world software powerhouse in the future, including the ever changing environment of the software market, as some regard as maelstrom effect. This paper describes the steps should be taken to establish the Microsoft Research Centre in Indonesia and the link to make Indonesia as a world software exporter.